(untitled) (World Economics and Finance Bulletin, 2024)
The objective of the current research is to study the understanding of cognitive styles and their impact on strategic professionalism in the researched university. Wherein the researcher developed a questionnaire based on previous studies related to the subject of the current study. The study sample consisted of (96) individuals from senior leadership in the university. Advanced statistical software was utilized to achieve the objectives of the current research. The results of the current research indicated a significant impact between the variable of cognitive styles and strategic professionalism. The current research recommends that senior leadership in the university conduct continuous training courses and programs to develop and disseminate a culture of professionalism among the human element in all fields and tasks entrusted to them.